Spitting on diamonds a spitball pitcher's journey to the major leagues, 1911-1919 - Hogg, Clyde H., 1941-; ebrary, Inc. (Columbia, Mo. : University of Missouri Press, 2005)
"Biography of early twentieth-century baseball pitcher, Bradley Hogg"--Provided by publisher.
Includes bibliographical references (p. 308-313) and index.
Electronic reproduction.
Keywords: Hogg, Bradley, -- 1888-1935.; Baseball players -- United States -- Biography; Electronic books